Haemodynamic Effects of Anaemia in Patients with Acute Decompensated Heart Failure - Paweł Krzesiński; Agata Galas; Grzegorz Gielerak; Beata Uziębło-Życzkowska (Cardiology Research and Practice)
Anaemia is a common comorbidity in patients with heart failure (HF) and is associated with more severe symptoms and increased mortality. The aim of this study was to evaluate haemodynamic profiles of HF patients with respect to the presence of reduced left ventricular ejection fraction (LVEF) and anaemia. Methods and Results. Haemodynamic status was evaluated in 97 patients with acute decompensated HF. Impedance cardiography, echocardiography, and N-terminal probrain natriuretic peptide (NT-proBNP) results were analysed. The study group was stratified into four subgroups according to LVEF (<40% vs ≥40%) and the presence of anaemia (haemoglobin <13.0 g/dL in men and <12.0 g/dL in women). Thoracic fluid content was higher (p=0.037) in anaemic subjects, while no significant relation between anaemia and NYHA was observed. Anaemic subjects with LVEF ≥ 40% were distinguished from those with LVEF < 40% by significantly higher stroke index (p=0.002), Heather index (p=0.014), and acceleration index (p=0.047). Patients with reduced LVEF and anaemia presented the highest NT-proBNP (p=0.003). Conclusions. In acute decompensated HF, anaemia is related with fluid overload, relatively higher cardiac systolic performance but no clinical benefit in patients with preserved/midrange LVEF, and increased left ventricular tension, fluid overload, and impaired cardiac systolic performance in patients with reduced LVEF.